Mercury Contamination of skin whiteners in cambodia - Thomas Murphy (2018)
Eleven of 41 brands of skin whiteners that were collected in Phnom Penh, Cambodia, and processed with a screening kit contained more than 2000 μg/g mercury. Risk analysis indicates that these 11 brands were toxic. Nine of 19 of these skin whiteners analyzed with cold vapor atomic absorption (CVAA) spectrophotometry exceeded Association of Southeast Asian Nations (ASEAN) guidelines for cosmetic good manufacturing practice limit on mercury of 1 μg/g. The most contaminated whitener analyzed by CVAA had 12,590 μg/g mercury. The mercury-containing products were labeled as produced in Thailand, China, Taiwan, Vietnam, the United States, and an unidentified country. Eight other products (antifungal, steroids, and antibiotics) were sold as additives to be mixed into whitener concoctions. In the 19 samples analyzed with CVAA, there was a significant association between the mercury content and a label "for export only." Labeling of sampled products varied from detailed to slight, with none containing Khmer instructions. Variability in mercury content of some products appeared to reflect copying of brand names with very similar packaging. © Taylor & Francis Group, LLC.